Influence of Cr substitution on the reversibility of the magnetocaloric effect in Ni-Cr-Mn-In Heusler alloys - Salazar-Mejía C.; Devi P.; Singh S.; Felser C.; Wosnitza J. (My University, 2025)
We present the effect of substitution-induced pressure on the reversibility of the magnetocaloric effect (MCE) in Ni2CrxMn1.4-xIn0.6 (x=0.1, 0.2, 0.3) alloys, through characterization in pulsed magnetic fields. We measured the adiabatic temperature change ΔTad directly during applied magnetic field pulses of 2 and 6 T. We paid special attention to the reversibility of ΔTad. The substitution of Mn by Cr in Ni2Mn1.4In0.6 leads to a negative pressure, as evidence by the increase of the lattice parameters, which shifts the martensitic transition towards lower temperatures and enhances the ferromagnetism of the martensite phase. We found a large value of ΔTad=-7 K at T=270 K for the sample with x=0.1 for a field change of 6 T. We discuss the reversibility of the MCE in these alloys in terms of the Clausius-Clapeyron equation. ©2021 American Physical Society.